PENGARUH KOMPLEKSITAS TUGAS, TEKANAN WAKTU, DAN LOCUS OF CONTROL TERHADAP KINERJA AUDITOR PADA INSPEKTORAT PROVINSI BENGKULU - Irwansyah, Irwansyah; Coryanata, Isma; Sukardi, Sukardi (JURNAL FAIRNESS, 2021)
This study aims to examine and analyze the effect of task complexity, timepressure, and locus of control on the performance of auditors at the Bengkulu Province Inspectorate. The data used in this study is primary data. The population in this study is the auditor inspectorate in Bengkulu Province.Sample selection was conducted using non-probability sampling, namely the convenience sampling method. The analytical method used is multiple linearregression. The results of the study indicate that task complexity, time pressure, and locus of control affect the performance of auditors at the Bengkulu Province Inspectorate.